Adoption and nonadoption of minimum tillage potato cultivation resulting from mechanized rice farming in Vietnam - Kawarazuka, Nozomi; Bui, Trang; Phung, Ha Trang (2025)
Minimum tillage potato production with rice straw mulching was widely promoted in Vietnam during the 2010s for efficient land use in the winter fallow season. This study evaluates the current adoption status 15 years after its introduction by a qualitative case study consisting of desk review, phone interviews and in-depth interviews, and field observation. Findings reveal that the original practice has been discontinued after initial adoption, primarily attributed to the adoption of rice harvesters and power tillers. The reasons for discontinuation differ from those for other conservation agriculture practices like zero tillage maize or wheat production, emphasizing the importance of tailored approaches for each crop and locality. Some farmers have adapted the method to fit their specific conditions in which the principles of conservation agriculture have been maintained. Those findings underscore the need for continual refinement of agricultural innovations along with socioeconomic and agroecological changes. Drawing on insights from the case of Vietnam, the study proposes a scaling strategy for South Asia where there is increasing interest in promoting potato zero tillage rice straw mulching.